Community-led regeneration : a toolkit for residents and planners - Sendra, Pablo; Fitzpatrick, Daniel (UCL Press, 2020)
Community-Led Regeneration draws on seven London case studies to offer a toolkit that residents and planners working with communities can use to resist demolition and propose community-led housing schemes.